Strategi Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru - Khair, Umamul; Faza, Najmi (Kartika: Jurnal Studi Keislaman, 2025)
The teaching profession is a functional position that requires specialized expertise in the field of education. Consequently, the role of a teacher cannot be effectively carried out by individuals lacking professional competence. This study aims to examine the leadership strategies employed by school principals in enhancing teacher professionalism at MTs Nurul Asrar Panggung, Sumenep. The research adopts a qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation. The findings indicate that the principal effectively implements leadership strategies through communicative approaches, continuous guidance, and professional development programs. These strategies have a positive impact on improving work discipline, institutional commitment, sense of responsibility, and the expansion of teachers’ pedagogical knowledge. However, the study also reveals ongoing challenges in achieving full professionalism, particularly concerning academic qualifications and the alignment between teachers’ educational backgrounds and their teaching subjects. Therefore, advancing teacher professionalism requires a more comprehensive effort, including the strengthening of school leadership and institutional policies that support sustainable competency development.